Prediction of Academic Performance Based on Learning Orientation: A Mixed Method Study in Malaysia and Australia - Paimin, Aini Nazura; J., Kaya Prpic; Roger G. , Hadgraft; Mohd Nusa, Fatin Najwa (Journal of Technical Education and Training, 2023)
The issue of high dropout rates in higher education, including in engineering, has led to some researchers focusing their research on understanding the relationship between students’ learning approaches and academic performance The current study adds to the current literature in this area to deepen our understanding of the role of learning orientation in the study success of engineering students. While technology-based learning approaches are becoming more popular, students nowadays are expected to be more independent and autonomous in learning. This study applied a concurrent mixed method design to get the breadth and in-depth information about learning strategies involved in the learning processes of engineering students. A revised version of the R-SPQ-2F learning orientation instrument was used to explore the learning strategies of 135 and 132 final-year engineering students at an institution in Malaysia and Australia respectively. The quantitative data were analysed using SPSS version 22 to inform the most important learning strategies used. The findings are further explained using data from semi-structured interviews which were conducted with similar participants. The information gained from both studies contributes to a deeper understanding of factors contributing to the study success of the engineering students at the two universities. The finding provides answers and reasoning to the differences in the learning strategies of students in both learning contexts and suggests strategies for universities to help improve students' learning experiences in engineering programs. Special attention is highlighted to the inclusion of the conative element that is always neglected in much research for further consideration by researchers who conduct similar research.